2019
DOI: 10.1038/s41467-019-11078-z
|View full text |Cite
|
Sign up to set email alerts
|

Boosting NAD+ with a small molecule that activates NAMPT

Abstract: Pharmacological strategies that boost intracellular NAD + are highly coveted for their therapeutic potential. One approach is activation of nicotinamide phosphoribosyltransferase (NAMPT) to increase production of nicotinamide mononucleotide (NMN), the predominant NAD + precursor in mammalian cells. A high-throughput screen for NAMPT activators and hit-to-lead campaign yielded SBI-797812, a compound that is structurally similar to active-site directed NAMPT inhibito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
130
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(137 citation statements)
references
References 31 publications
4
130
1
Order By: Relevance
“…635,637,638 SBI-797812 activates NAMPT via stabilizing the NAMPT phosphorylation at His247, enhancing the efficiency of NMN generation, providing another option to raise NAD + . 639 Together, the NAMPT enhancers, P7C3 and SBI-797812, warrant further study for the clinical treatment of neuron related diseases.…”
Section: Inhibition Of Nad + Consumptionmentioning
confidence: 99%
“…635,637,638 SBI-797812 activates NAMPT via stabilizing the NAMPT phosphorylation at His247, enhancing the efficiency of NMN generation, providing another option to raise NAD + . 639 Together, the NAMPT enhancers, P7C3 and SBI-797812, warrant further study for the clinical treatment of neuron related diseases.…”
Section: Inhibition Of Nad + Consumptionmentioning
confidence: 99%
“…3A). We next determined if the PARP10-mediated loss in NAD + could be restored by increasing cytosolic NAD + synthesis with SBI, a small molecule activator of NAMPT, which promotes NAM salvage (23). SBI enhanced NAD + synthesis in GFP expressing cells, but did not significantly enhance NAD + in PARP10 expressing cells, indicating that PARP10 expression is sufficient to limit cellular NAD + (Fig.…”
Section: Parp10 Overexpression Is Sufficient To Depress Nad + Levelsmentioning
confidence: 99%
“…Here we show that PARP10 overexpression is sufficient to depress cellular NAD + and that the MARylating activities of PARP10, PARP12 and PARP14 can be pharmacologically increased by enhancing NAD salvage synthesis (salvage?) with SBI-797812 (SBI), a NAMPT activator (23).…”
mentioning
confidence: 99%
“…Different studies identified small molecules able to enhance NAMPT expression, such as P7C3, and ultimately NAD + cellular content [ 98 ]. More recently, SBI-797812 has been identified as a NAMPT activator, which increased levels of NAD + in the heart of treated mice [ 99 ].…”
Section: Clinical Perspectives Targeting Nad +mentioning
confidence: 99%